Pengembangan Media Pembelajaran Berbasis Web untuk Bahasa Inggris di Sekolah Dasar - Muh. Hafidz; Rasmiati Rasyid; I Gede Purwana Edi Saputra (GJET : Global Journal of Educational Technology, 2024)
This study seeks to create web-based interactive learning media to improve students' comprehension of the Simple Past Tense and Simple Future Tense at SDN 1 Lamoiko. The material was created utilizing the ADDIE development paradigm (Analyze, Design, Development, Implementation, Evaluation) and web technologies like PHP, HTML, CSS, and JavaScript. Evaluation was performed by User Acceptance Testing (UAT) and N-Gain analysis to assess the efficacy of the medium. The UAT results indicated a teacher satisfaction rating of 85%, classified as "very good." Simultaneously, the average N-Gain score attained 0.76, signifying a "high" level of enhancement in pupils' comprehension. This educational media encompasses features like animations, quizzes, and instructional games aimed at enhancing student participation in the learning process. In summary, this medium effectively aids students in comprehending English content and can be modified for wider application